LEVEL UP! THE AI ACCOUNTING COMPETENCY MATRIX. A PROPOSAL FOR DEVELOPING THE SKILLS OF MODERN ACCOUNTING PROFESSIONALS - Réka Melinda TÖRÖK; Andreea IURAȘ; Victoria BOGDAN (Oradea Journal of Business and Economics, 2025)
This article explores the key skills needed for the effective integration of artificial intelligence (AI) into accounting. Against the backdrop of digital transformation, accounting professionals need to develop technical and analytical skills to capitalize on the opportunities offered by AI. Following rigorous qualitative research, a comprehensive competence matrix has been developed serving as a potential guide for accounting practitioners in the process of AI implementation at the level of the accounting system. In the first stage of the qualitative research, a content analysis of online publications belonging to IFAC and Big4 companies was conducted, focused on investigating the profile of AI skills needed in modern accounting. As a result of this analysis, twelve competencies were found, of which five were technical, five were soft, and two were related to legal compliance and management. The results of the qualitative investigation of IFAC and Big4 publications revealed that advanced data analysis, critical thinking, and adaptability are unanimously recognized as fundamental pillars in the development of AI competencies in accounting and financial reporting. In the second research stage, based on the content analysis of the aforementioned publications, an integrated competence matrix was developed which encompasses the key competencies required for adopting and leveraging AI in accounting. The integrated matrix is ​​structured on four levels and contains fifteen competencies. This matrix, built on four levels of competencies, fundamental, technical, psycho-socio-emotional, and strategic, synthesizes the fundamental directions of professional development and outlines a conceptual framework for the adaptation of accounting professionals to new technological challenges. This integrated approach allows for a clear understanding of how these competencies interconnect and support each other in the successful implementation of artificial intelligence in accounting.